The Fish Lands. German trade with Iceland, Shetland and the Faroe Islands in the late 15th and 16th Century - Holterman, Bart (De Gruyter, 2020)
The late medieval German trade with the North Atlantic islands, in the margins of the Hanseatic trade network, has received only limited scholarly attention. Merchants from predominantly Hamburg and Bremen established direct trade relations with these islands in the late 15th century, and managed to control the international trade with Iceland, the Faroes and Shetland for much of the 16th century. However, the Hanseatic commercial infrastructure was absent in the North Atlantic, which forced these merchants to develop new trade strategies. Besides a critical re-evaluation of the economic and political conditions, this volume offers a comprehensive study of the organisation of the trade and the methods used to establish and maintain networks between islanders and German merchants. Moreover, it analyses the role and socio-economic position of the communities of merchants with the North Atlantic in their home towns. The book shows that the North Atlantic trade was anything but insignificant. It was a dynamic and integral part of the trade network of the northern German cities, and its study is highly relevant for the economic history of Northern Europe.